Posterior ankle and hindfoot endoscopy: A cadaveric study. Issue 3 (September 2016) - Lui, T.H.; Chan, L.K.
Abstract: Background: The list of indications of posterior ankle endoscopy is expanding and includes various soft tissue and bony pathologies of the posterior ankle. Some of the indications, e.g. release of frozen ankle, debridement of posteromedial soft tissue impingement of the ankle and debridement or fixation of the posteromedial osteochondral lesion of the talus, require approach to the posterior ankle medial to the flexor hallucis longus tendon. The purpose of this study was to assess the risk of injury to the posterior tibial neurovascular bundle during posterior ankle endoscopy. Methods: Fourteen fresh frozen foot and ankle specimens were used. A metal rod was inserted into the posteromedial, posterolateral and modified posteromedial portals and touched the medial border of the posterolateral talar tubercle and the posteromedial corner of the ankle mortise in turn. The neurovascular bundle and FHL tendon were examined for any kink. Results: The neurovascular bundle was kinked in all specimens (100%) with the rod at the posteromedial corner of the ankle mortise through the posteromedial portal and was kinked in 11 specimens (79%) with the rod through the modified posteromedial portal. The neurovascular bundle was kinked in 1 specimen (7%) with the rod through the posterolateral portal. Conclusions: The neurovascular bundle was at risk during instrumentation of the posteromedial ankle through the posteromedial portal but was safe through the posterolateral portal.